Disease-modifying trials in Alzheimer's disease: a European task force consensus. - Vellas, B; Andrieu, S; Sampaio, C; Wilcock, G (2007)
After symptomatic treatments, the new target for therapeutic approaches in Alzheimer's disease is the development of disease-modifying drugs. The concept of disease modification in Alzheimer's disease is controversial and the design of these trials raises many questions. Which populations should be studied? For how long? With which principal and secondary endpoints? Are surrogate markers available? Here, we present a European consensus on disease-modifying trials in Alzheimer's disease, agreed under the auspices of the European Alzheimer's Disease Consortium and based on the European perspective of the concept of disease modification, study designs, the role for biomarkers, risk benefit, and pharmacoeconomic issues.